2013
DOI: 10.1186/1477-7525-11-99
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socio-economic status on health related quality of life for children and adolescents with heart disease

Abstract: BackgroundSocioeconomic status (SES) is known to influence children’s health-related quality of life. Many SES indicators assess distinct dimensions of a family’s position rather than measuring the same underlying construct. Many researchers, however, see SES indicators as interchangeable. The primary aim of this study was to determine which measure of SES had the strongest impact on health-related quality of life.MethodsThis is a secondary analysis of the Pediatric Cardiac Quality of Life Inventory Validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 32 publications
7
50
0
3
Order By: Relevance
“…Recently, societal factors such as poverty, medical insurance, and maternal education have emerged as predictors of adverse outcomes in children with complex congenital heart disease (CHD) and may explain some of the difference in survival between children with similar clinical characteristics 9. Specifically, low socioeconomic status (SES) in children with SV physiology has been associated with higher early mortality6, 8 and lower quality of life10 after surgery, and other studies have found similar associations in the larger CHD population 11, 12, 13, 14, 15, 16. Nevertheless, existing studies examining SES have been limited by cross‐sectional or case–control study designs,14, 15 single center populations,7, 9, 10, 14, 15 or limited outcome assessment 6, 8.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, societal factors such as poverty, medical insurance, and maternal education have emerged as predictors of adverse outcomes in children with complex congenital heart disease (CHD) and may explain some of the difference in survival between children with similar clinical characteristics 9. Specifically, low socioeconomic status (SES) in children with SV physiology has been associated with higher early mortality6, 8 and lower quality of life10 after surgery, and other studies have found similar associations in the larger CHD population 11, 12, 13, 14, 15, 16. Nevertheless, existing studies examining SES have been limited by cross‐sectional or case–control study designs,14, 15 single center populations,7, 9, 10, 14, 15 or limited outcome assessment 6, 8.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][10][11][12] In Sweden, HF hospitalisation rates were 45% higher in individuals on low income than those on high income. [10] In the First National Health and Nutrition Examination Survey in the United States, low education was associated with high HF hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 1,383 patients (695 children and 688 adolescents) with heart disease from seven large paediatric cardiac centres in the United States, Cassedy et al [4] found that family income was the strongest predictor of health related quality of life for the patients. In a review, Calvillo-King et al [5] reported that low income and low education increased the risk for readmission among HF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Stress in terms of finances, emotional drain, and family member burden are reported in the literature [39][40][41]. Based on practical experience over greater than 20 years of nursing experience, the CHD ISSN: 2380-0534 families of today comprise a mixture of dual income households with more financial health care coverage concerns and often less extended family in close proximity.…”
Section: Conclusion Changing Population Of Chdmentioning
confidence: 99%